Pemikiran Pendidikan John Dewey - Nur Arifin (Fakultas Syariah IAIN Laa Roiba Bogor, 2020)
ABSTRACT According to John Dewey, education is a process of forming fundamental fundamental abilities, both concerning thinking (intellectually) and feeling power (emotionally), leading to human and ordinary human nature. Education as a rearrangement or reconstruction of various experiences and events experienced in an individual's life so that everything new becomes more focused and meaningful. John Dewey adheres to pragmatism. That is, the educational process is only about ideas that can be put into practice that are correct and useful. Ideas that exist only in ideas are also indecisive about the reality of sense objects, they are nonsense to pragmatism. The philosophy of thinking about education is reflective thinking, which is a way of thinking that starts from the problems that are faced with it to be solved. According to John Dewey, learning should be focused on practice and trial and error. Humans must be active, full of interest, and ready to explore. Therefore education must be restructured not only as preparation for maturity, but education as a continuation of the growth of the mind and the continuation of life light. Education is directed at social efficiency by providing the ability to participate in activities for the fulfillment of common interests and welfare freely and maximally. John Dewey criticized a lot of traditional education patterns, namely education patterns that make children the object of education, not the subject of education. He does not agree with the concept of traditional education, which states that the focus of education is outside children, whether it be teachers, books, infrastructure, or others. Because the concept of traditional education makes school a formal place for listening, for mass instruction, and separate from life. Traditional education patterns will not be able to see children as living things that grow in their own experiences and then develop them in an environment in accordance with their basic potential. Therefore education needs to be organized in a democratic manner. All adult students are encouraged to participate in shaping the values ​​that govern life together. The science of education cannot be separated from philosophy, that the purpose and aim of the school is to generate a democratic attitude to life and to develop it.